Isolation and characterisation of theobromine-degrading filamentous fungi - Oduro-Mensah, D.; Ocloo, A.; Lowor, S.T.; Bonney, E.Y.; Okine, L.K.N.A.; Adamafio, N.A. (Microbiological Research, 2018)
Strategies for achieving global food security include identification of alternative feedstock for use as animal feed, to contribute towards efforts at increasing livestock farming. The presence of theobromine in cocoa pod husks, a major agro-waste in cocoa-producing countries, hinders its utilisation for this purpose. Cheap treatment of cocoa pod husks to remove theobromine would allow largescale beneficial use of the millions of metric tonnes generated annually. The aim of this study was to isolate theobromine-degrading filamentous fungi that could serve as bioremediation agents for detheobromination of cocoa pod husks. Filamentous fungi were screened for ability to degrade theobromine. The most promising isolates were characterized with respect to optimal environmental conditions for theobromine degradation. Secretion of theobromine-degrading enzymes by the isolates was investigated. Theobromine degradation was monitored by HPLC. Of fourteen theobromine-degrading isolates collected and identified by rDNA 5.8S and ITS sequences, seven belonged to Aspergillus spp. and six were Talaromyces spp. Based on the extent of theobromine utilization, four isolates; Aspergillus niger, Talaromyces verruculosus and two Talaromyces marneffei, showed the best potential for use as bioagents for detheobromination. First-time evidence was found of the use of xanthine oxidase and theobromine oxidase in degradation of a methylxanthine by fungal isolates. Metabolism of theobromine involved initial demethylation at position 7 to form 3-methylxanthine, or initial oxidation at position 8 to form 3,7-dimethyuric acid. All four isolates degraded theobromine beyond uric acid. The data suggest that the four isolates can be applied to substrates, such as cocoa pod husks, for elimination of theobromine.
Keywords: Aspergillus; Biodetheobromination; Cocoa pod husk; HPLC; ITS-PCR; Theobromine